Modified laparoscopic transvesical diverticulectomy: a case series study for the treatment of giant bladder diverticulum - Jianyu Wang; Xiaoran Han; Shanhua Zhang; Shaoqiu Kong; Feifan Liu; Cheng Wang; Haihu Wu; Fei Wu; Jiaju Lyu; Hao Ning (BMC Urology)
Abstract Background​ Bladder diverticulum presents significant surgical challenges in traditional laparoscopic approaches, including difficulty in locating diverticular openings and risks of ureteral injury. This study introduces a novel “modified laparoscopic transvesical diverticulectomy” featuring an inside-out approach with CO2 gas bladder insufflation, addressing these limitations and offering an innovative minimally invasive solution for giant bladder diverticula. Case series​ Between 2022 and 2024, a case series of 10 patients (9 males, 1 female; mean age 70.6 years) underwent the modified procedure. Among them, 3 patients simultaneously underwent the modified procedure and transurethral resection of the prostate (TURP), while the remaining 7 patients underwent the modified procedure alone. The diverticula (mean maximum diameter: 5.94 cm) were predominantly located on the posterior bladder wall (8 cases, 80%). For 7 patients undergoing isolated diverticulectomy, mean operative time was 1.13 h with 7.86 ml blood loss. Postoperative hospitalization averaged 4.29 days, and catheter retention lasted 9.29 days. Three patients with concurrent transurethral prostate resection showed prolonged operative time (2.73 h). The 30-day complication rate was 14.3% (1 case of deep vein thrombosis). All patients demonstrated significant symptom resolution without recurrence during follow-up. Conclusions​ This modified technique enhances surgical precision through cystoscopic visualization and CO2 insufflation, achieving shorter operative duration (40% reduction vs. traditional methods), minimal blood loss (< 8 ml), and low complication rates. Its simplified workflow and compatibility with concurrent prostate surgery make it particularly advantageous for complex cases. This study establishes a promising paradigm for giant bladder diverticulum management, warranting further validation through larger cohorts and long-term follow-up.